Concepts and Principles of Da'wah in The Frame of Islamic Community Development - Malik Ibrahim; Agus Riyadi (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
This study aims to analyze how the concepts and principles of da'wah develop Islamic society. This research uses a type of qualitative research with a literature approach and with literature study methods. The study results show that the concept of da'wah for empowering the Islamic community prioritizes the example and ethics of a preacher. Besides that, it focuses more on da'wah with a series of activities that can improve people's welfare regarding economy, development, and technology. Meanwhile, the principle of community development da'wah uses the tenets of ukhuwwah, Ta'awun, justice, participation, and equality.